Pengaruh ROA, DER, dan EPS Terhadap Return Saham (Studi Kasus pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Periode 2018-2022) - Ramadhini, Diva Carisa; Apriliasari , Ria Dini; Muhdor , Ali; Devi, Fitriyah Kusuma (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
In this increasingly modern era, many people invest in addition to getting profits, it can also maintain the value of money or wealth from inflation. The purpose of this study is to determine how ROA, DER, and EPS impact the stock returns of companies in the financial sector listed on the Indonesia Stock Exchange from 2018 to 2022. The population in this study were banking sub-sector financial sector companies listed on the IDX for the period 2018-2022, this sample was determined by purposive sampling technique, with predetermined criteria, so that 35 banking sub-sector financial sector companies were obtained that qualified as samples. The secondary data used in this study are historical data from the company's financial statements. Quantitative methods are used in this study. The results showed that the ROA and DER variables did not affect stock returns partially (t-test). While the EPS variable influences stock returns partially (t-test). Simultaneously (f test) the independent variables, namely, ROA, DER, and EPS have a joint influence on stock returns.